Two Catechol Siderophores, Acinetobactin and Amonabactin, Are Simultaneously Produced by Aeromonas salmonicida subsp. salmonicida Sharing Part of the Biosynthetic Pathway - Balado, Miguel (2015)
The iron uptake mechanisms based on siderophore synthesis used by the fish pathogen Aeromonas salmonicida subsp. salmonicida are still not completely understood, and the precise structure of the siderophore(s) is unknown. The analysis of genome sequences revealed that this bacterium possesses two gene clusters putatively involved in the synthesis of siderophores. One cluster is a candidate to encode the synthesis of acinetobactin, the siderophore of the human pathogen Acinetobacter baumannii, while the second cluster shows high similarity to the genes encoding amonabactin synthesis in Aeromonas hydrophila. Using a combination of genomic analysis, mutagenesis, biological assays, chemical purification, and structural determination procedures, here we demonstrate that most A. salmonicida subsp. salmonicida strains produce simultaneously the two siderophores, acinetobactin and amonabactin. Interestingly, the synthesis of both siderophores relies on a single copy of the genes encoding the synthesis of the catechol moiety (2,3-dihydroxybenzoic acid) and on one encoding a phosphopantetheinyl transferase. These genes are present only in the amonabactin cluster, and a single mutation in any of them abolishes production of both siderophores. We could also demonstrate that some strains, isolated from fish raised in seawater, produce only acinetobactin since they present a deletion in the amonabactin biosynthesis gene amoG. Our study represents the first evidence of simultaneous production of acinetobactin and amonabactin by a bacterial pathogen and reveals the plasticity of bacterial genomes and biosynthetic pathways. The fact that the same siderophore is produced by unrelated pathogens highlights the importance of these systems and their interchangeability between different bacteria.